2010
DOI: 10.1038/hr.2010.235
|View full text |Cite
|
Sign up to set email alerts
|

ACE2–angiotensin-(1–7)–Mas axis and oxidative stress in cardiovascular disease

Abstract: The renin-angiotensin-aldosterone system (RAAS) is a pivotal regulator of physiological homeostasis and diseases of the cardiovascular system. Recently, new factors have been discovered, such as angiotensin-converting enzyme 2 (ACE2), angiotensin-(1-7) and Mas. This newly defined ACE2-angiotensin-(1-7)-Mas axis was shown to have a critical role in the vasculature and in the heart, exerting mainly protective effects. One important mechanism of the classic and the new RAAS regulate vascular function is through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 94 publications
6
122
0
3
Order By: Relevance
“…ACE2 converts Ang II to angiotensin-1-7 (Ang- (1-7)), which increased NO release from endothelial cells through its receptor Mas, thus resulting in vasodilation. 32 As olmesartan reportedly increased aortic ACE2 and Ang-(1-7) in conjunction with improved vascular remodeling in spontaneously hypertensive rats, 33 the effect of olmesartan on endothelial function might be mediated by this pathway. In the present study, olmesartan significantly improved endothelial function as compared with baseline and amlodipine (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 converts Ang II to angiotensin-1-7 (Ang- (1-7)), which increased NO release from endothelial cells through its receptor Mas, thus resulting in vasodilation. 32 As olmesartan reportedly increased aortic ACE2 and Ang-(1-7) in conjunction with improved vascular remodeling in spontaneously hypertensive rats, 33 the effect of olmesartan on endothelial function might be mediated by this pathway. In the present study, olmesartan significantly improved endothelial function as compared with baseline and amlodipine (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…5 One important mechanism of vascular remodeling is via oxidative stress induced by the ACE/Ang II/AT 1 receptor axis, and the ACE2/Ang-(1-7)/Mas axis has also been reported to be involved in the regulation of oxidative stress. 19 For instance, it has been reported that MasKO mice from 2 different genetic backgrounds showed a reduction in superoxide dismutase and catalase activity, suggesting impaired antioxidant properties in these animals. 20 In addition, it is reported that the vasoprotective and atheroprotective effects of Ang-(1-7) are mediated by the restoration of nitric oxide bioavailability in apolipoprotein E-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 promoted capillary and neovessel maturation and reduced atherosclerosis, and attenuated AngⅡ-induced reactive oxygen production in part through decreasing the expression of p22 phox in an Ang-(1-7)-dependent fashion. And we would like to refer details to reviews that report the relationship ACE2/ Ang-(1-7)/Mas Axis with oxidative stress [46,47]. Interactions between AT 1 receptor, Mas and NAD(P)H oxidase at signal transduction level from above mentioned reports [43] are summerized in Figure 2.…”
Section: Ace2/ Ang-(1-7)/ Mas Axismentioning
confidence: 99%